Global Talent Management - Zerroug, Yassamina (جامعة الوادي - University of Eloued, 2021)
ملخّص : التحديات التي تواجه إدارة المواهب العالمية في اعمال المنظمات الجزائرية هدفت هذه الدراسة الى تحديد مفهوم إدارة المواهب من المنظور العالمي كضرورة ملحة في القرن الحادي والعشرين. ومن اجل الإجابة على إشكالية الدراسة وتساؤلاتها الفرعية قمنا بالتطرق لواقع إدارة الموارد البشرية في منظمات الاعمال الجزائرية من اجل التوصل الى ملاحظات تساعدها في التعرف على المواهب التي تحملها القوى العاملة الجزائرية وقيادتها لتحقيق مستويات أعلى من الأداء المؤسسي. توصلت الدراسة في الأخير على مجموعة من النتائج أهمها ان منظمات الاعمال الجزائرية لابد عليها من تسليط الضوء على المواهب الموجودة ضمن كوادرها البشرية والعامل على الاستثمار فيها بالطريقة الصحيحة التي من شانها في النهاية الرفع من مستوى أدائها واكتسابها صبغة دولية تمكنها من المنافسة على مختلف الأصعدة الدولية وتمنح المؤسسات الجزائرية ميزة تنافسية عالمية . Abstract: Global Talent Management: the challenge that knocks The doors of Algerian Organisations This study aimed to precise the identification of Global Talent Management (GTM) as an urgent necessity in the 21st century. In order to answer the problematic study we tried to apply a speed reading on the reality of human resource management in the Algerain organizations to conclude some remarks that can help them in extracting and leading the talent existing in Algerian workforce towrds a high level of performance. The study concluded at the last a set of results, the most important are: the algerian Organizations should shed the light on the talents that exist and invest in it in the right way to improve the level of performance and build an international competitive advantage
The Challenge That Knocks The Doors Of Algerian Organisations
مقال
Keywords: المواهب,إدارة المواهب,إدارة المواهب العالمية; Talent; Talent Management ; Global Talent Management